The Quality and Antioxidant Content of Salted Eggs Made By Addition of Bay Leave Crude Extract on the Salting Media - Agustina, Kadek Karang; Mardyawati, Ida Ayu Putu Aselya; Suada, I Ketut (Advances in Tropical Biodiversity and Environmental Sciences; Vol 3 No 2 (2019): ATBESDO - 10.24843/ATBES.2019.v03.i02.p05, 2019)
This research aims to produce salted eggs with antioxidant content from bay leave extract. The study used a completely randomized design (CRD) in which there were 3 treatments, namely, control with 0% bay leaf extract, treatment 1 with adding 25% crude extract of bay leaves, and treatment 2 with a 50% addition of crude bay leaf extract. All treatments were pressed for 14 days before testing. The parameters observed in the study were the antioxidant capacity, albumin index, yolk index, and Haugh unit. The results show that the sated eggs with the different concentration of bay leave extract contain antioxidant 4.445%, 30.853%, and 44.32% respectively, albumin index of treated eggs was lower than control, while Haugh unit of treated eggs was higher than control, and no differentiation of yolk index between the treatments. To conclude, the addition of bay leave crude extract can increase the value of salted eggs without disturbing the quality.